Otimização da extração de sesquiterpenos de Zingiber officinale roscoe e avaliação do seu potencial biológico frente a fatores de virulência de bactérias - Santos, Jussara Oliveira dos (2019)
Ginger (Zingiber officinale Roscoe) is a medicinal plant known for its anti-inflammatory, antitumoral, antioxidant and antimicrobial properties. The objective of this study was to optimize the extraction of sesquiterpenes (α-curcumene, α-zingiberene, α-farnesene, β-sesquifelandrene and β-bisabolene), to evaluate their antimicrobial and antibiotic potential against Staphylococcus aureus, Streptococcus mutans, S. agalactiae, Escherichia coli and Pseudomonas aeruginosa, in addition to their antiproteic activity. Analyzes of the extracted compounds were performed by GC-MS. Antimicrobial and biofilm formation assays were performed by the 96 well plate microdilution technique. In addition to assessing biofilm inhibition, the hydrophobicity index was also determined as an indirect way of assessing the ability of microorganisms to adhere to host tissues and abiotic surfaces. The best conditions for obtaining the sesquiterpene-enriched fraction (SEF) were: extraction time: 4 min, plant / solvent ratio: 1:20 (m / v) and microwave power: 400 W. The SEF presented a MIC of 2000 μg / mL compared to S. mutans and was ineffective in inhibiting the growth of other bacteria. Nevertheless, SEF (250 μg / mL) inhibited the biofilm formation of S. aureus, S. agalactiae and E. coli by 50%, 80% and 80%, respectively. In addition, and E. coli bacteria by 61.86%, 73.44% and 49.10%, respectively. FES (500 μg / mL) was able to reduce papain enzymatic activity by 71.5%, with an IC50 of 386.8 μg / mL. The results showed that SEF had potential to combat the production of bacterial biofilms. Thus, these substances are good candidates for drug prototypes used to treat infections caused by multi-resistant bacteria. To our knowledge, this is the first time that the SEF antimicrobial and antibiofilm activity has been studied.